173 CATERPILLAR SIGN: NOVEL ENDOSCOPIC FINDING IN PATIENTS WITH EOSINOPHILIC ESOPHAGITIS. (17th September 2021) - Ayaki, Maki; Manabe, Noriaki; Haruma, Ken; Nakamura, Jun; Fujita, Minoru; Suehiro, Mitsuhiko; Kawamoto, Hirofumi; Kamada, Tomoari; Yamatsuji, Tomoki; Naomoto, Yoshio
Abstract: : Pathological identification of esophageal eosinophilia (EE) is considered to be most important and critical step for diagnosis of eosinophilic esophagitis (EoE). Although several endoscopic findings related with EoE have been reported, it is still difficult to exclude other causes of EE, such as gastroesophageal reflux disease. Here, we noted a novel endoscopic finding related with EoE termed 'Caterpillar sign'. The aim of this study was to evaluate its clinical significance for the diagnosis of EoE. Methods: One hundred and seventy-four patients who were endoscopically suspected with EoE at our hospital and affiliated institutions were enrolled. EoE was defined clinically by symptoms of esophageal dysfunction and histologically by the presence of EE [≧15 eosinophils/high power field (HPF)]. Endoscopic findings at baseline were retrospectively reviewed. 'Caterpillar sign' was defined as a stair-like, fragile, slight mucosal protruded lesion sandwiched between longitudinal furrows, such as the Caterpillar traces remaining on the ground (Figure). Furthermore, the clinicopathological features of patients having 'Caterpillar sign' were evaluated. Results: One hundred and seventy-four patients (92 males, 82 females with mean age of 49.7) suspected with EoE were evaluated, of whom 60 (34.5%) was finally diagnosed as EoE. 'Caterpillar sign' was found in 48 patients (80.0%). Sensitivity and Specificity of 'Caterpillar sign' for the diagnosis of EoE was 0.80 (95% confidence interval [CI] 0.72–0.85) and 0.94 (95% CI 0.90–0.97), respectively. Furthermore, the presence of 'Caterpillar sign' was associated with degree of eosinophil infiltration (Caterpillar sign positive: 42.9 ± 49.3/HPF vs. Caterpillar sign negative: 6.7 ± 24.4/HPF, p < 0.0001). Conclusion: This novel finding termed 'Caterpillar sign' was clinically useful for the definitive diagnosis of EoE and associated with degree of eosinophil infiltration.